Academic Self-efficacy and Academic Procrastination in adolescents from Quito, Ecuador - Pozo-Pozo, Diana Verónica (2023)
The objective was to determine the relationship between Academic Self-Efficacy and Academic Procrastination in a sample of adolescents from the city of Quito, Ecuador. The research presents a descriptive, correlational, and cross-sectional approach using the Academic Procrastination Scale, Tuckman's Academic Procrastination Scale, General Self-Efficacy, and Perceived Specific Academic Situations Self-Efficacy scales. Participated 424 adolescents (49.8% male, 50.2% female) aged between 12 and 17 years (M = 14 years; SD = 1.71). Students from different secondary educational institutions (73.8% private, 25.2% public, and 0.9% Fiscomisional, jointly funded by the government and the Catholic Church). General and Academic Self-Efficacy are moderate, while Procrastination is low; gender differences are only present in General Self-Efficacy, with males showing more self-efficacy. There is a relationship between Academic Self-Efficacy and Academic Procrastination. In conclusion, Academic Self-Efficacy is a relevant factor that allows the identification of Academic Procrastination in adolescents from the city of Quito.